2012
DOI: 10.1038/onc.2012.213
|View full text |Cite
|
Sign up to set email alerts
|

Opposing functions of Fbxw7 in keratinocyte growth, differentiation and skin tumorigenesis mediated through negative regulation of c-Myc and Notch

Abstract: The tumor suppressor Fbxw7 (also known as Sel-10, hCdc4, hAgo, or Fbw7) is an F-box protein that functions as the substrate-recognition subunit of an SCF ubiquitin ligase complex and targets a group of oncoproteins for degradation. We now show that Fbxw7 regulates the proliferation and differentiation of keratinocytes by mediating the degradation of c-Myc and Notch proteins. Fbxw7-deficient keratinocytes showed an increased proliferative capacity that was dependent on the accumulation of c-Myc but not on that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…The half-life of c-Myc in keratinocytes is regulated by the E3 ligases Fbxw7 (Ishikawa et al 2013) and Skp2 (Muller and Eilers 2008). For Fbxw7-mediated c-Myc degradation to occur, c-Myc must be phosphorylated on Thr 58 by ERK and on Ser 62 by GSKb (Muller and Eilers 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The half-life of c-Myc in keratinocytes is regulated by the E3 ligases Fbxw7 (Ishikawa et al 2013) and Skp2 (Muller and Eilers 2008). For Fbxw7-mediated c-Myc degradation to occur, c-Myc must be phosphorylated on Thr 58 by ERK and on Ser 62 by GSKb (Muller and Eilers 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, this more complex picture does not exclude the possibility that some E3 ligases could play a more critical role in the senescent phenotype. Indeed, as discussed previously, SCF-FBW7 is a well-known tumor suppressor and has been recently shown to contribute to senescence, 243,247,256 and correspondingly many FBW7 targets are degraded in SAPD. The CUL4A-DDB1 (SCF4) complex and its interacting receptor protein DDB2 are also strong candidates, since both have been shown to drive senescence.…”
Section: Kinases Vs Phosphatases and E3 Ligases Vs Deubiquitinases:mentioning
confidence: 95%
“…FBW7 mutants cannot bind to the NICD. Although the mutant forms of FBW7 were still able to bind to Myc, they do not target it for degradation [29,33]. In melanoma Notch expression is increased.…”
Section: F-box Proteinsmentioning
confidence: 97%
“…Numerous cancer-associated mutations in FBW7 and its substrates have been identified, and loss of FBW7 function causes chromosomal instability and tumorigenesis [29,30,32,33]. FBW7 mutation rates in cholangiocarcinoma, T-cell acute lymphocytic leukemia, endometrial carcinoma, and colorectal cancer were reported as 35%, 31%, 9%, and 9%, respectively [29,30,34].…”
Section: F-box Proteinsmentioning
confidence: 98%
See 1 more Smart Citation